Antimicrobial susceptibility of Flavobacterium psychrophilum isolates from the United Kingdom. Issue 2 (24th October 2017) - Ngo, T P H; Smith, P; Bartie, K L; Thompson, K D; Verner‐Jeffreys, D W; Hoare, R; Adams, A
Abstract: Routine application of antimicrobials is the current treatment of choice for rainbow trout fry syndrome (RTFS) or bacterial coldwater disease (BCWD) caused by Flavobacterium psychrophilum . In this study, the antimicrobial susceptibilities of 133 F. psychrophilum isolates, 118 of which were from the UK, were evaluated by broth microdilution and disc diffusion methods following VET04‐A2 and VET03‐A guidelines of Clinical and Laboratory Standards Institute (CLSI), respectively. Isolates were categorized as wild type (fully susceptible, WT) or non‐wild type (NWT) using normalized resistance interpretation (NRI)‐determined cut‐off values (COWT ). Broth microdilution testing showed that only 12% of UK isolates were WT to oxolinic acid (MIC COWT ≤ 0.25 mg/L) and 42% were WT for oxytetracycline (MIC COWT ≤ 0.25 mg/L). In contrast, all the isolates tested were WT (MIC COWT ≤ 2 mg/L) for florfenicol, the main antimicrobial for RTFS control in the UK. Disc diffusion‐based COWT values were ≥51 mm for 10 μg amoxicillin, ≥44 mm for 30 μg florfenicol, ≥30 mm for 2 μg oxolinic acid and ≥51 mm for 30 μg oxytetracycline. There was a high categorical agreement between the classifications of the isolates by two testing methods for florfenicol (100%), oxytetracycline (93%) and oxolinic acid (99%).